Turkish Version of Self Concept and Identity Measure (SCIM): Psychometric Properties - Emine Inan; Ozden Yalcinkaya Alkar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
In the current study, it is aimed to adapt Self-Concept and Identity Measure (SCIM) into Turkish. The participants of the study were internet users (n = 364). According to exploratory factor analysis results, Turkish version of SCIM (T-SCIM) consists of two factors (disturbed identity and consolidated identity). Moreover, T-SCIM showed expected correlations with emotion regulation, coping strategies, and psychopathologies. The internal consistency (Cronbachs α = 0.88) and test-retest reliability (α = 0.82, r = 0.70; ICC = 0.82) scores were found to be very good. It is concluded that T-SCIM is a reliable and valid scale that can be used in Turkey. [JCBPR 2016; 5(3.000): 111-118]